Communication Within Firms: Evidence from CEO Turnovers - Impink, Stephen Michael; Prat, Andrea; Sadun, Raffaella (Management Science, 2024)
This paper uses novel, firm-level communication measures derived from communications metadata several months before and after a CEO transition for 102 firms to study whether and how this organizational event is reflected in employees’ communication flows. We find that CEO turnover is associated with an initial decrease in intrafirm communication (−20% relative to the pre-CEO transition period), followed by a significant increase approximately five months after the CEO turnover (+20% relative to the pre-CEO transition period). The increase in communication is driven primarily by interdepartmental (i.e., communication involving employees of different functional departments) and vertical (i.e., communication among managers and employees) communication flows. This study suggests that communications metadata are a useful tool to examine how organizational change and related uncertainty impact information flows within firms. This paper was accepted by Alfonso Gambardella, business strategy. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.02719 .